Dissipative particle dynamics simulations of the morphologies and dynamics of linear ABC triblock copolymers in solutions1. Issue 71 (2nd August 2015) - Zhou, Chun; Xia, Honggang; Zhou, Yang; Xue, Xianggui; Luo, Shikai
<x xml:space="preserve">Abstract</x> Due to the great potential in the field of multifunctional nanoreactors and carriers, several previous works have shown the interesting morphologies of multicompartment micelles from simple linear ABC triblock copolymers in solutions.